Pathologies of Desire and Duty: Freud, Ricoeur, and Castoriadis on Transforming Religious Culture - Wahl, William H. (Journal of religion and health, 2008)
This article emphasizes an underappreciated aspect of Freud's critique of religion taken up in the writings of Ricoeur and Castoriadis: the degree to which pathologies of desire and duty imbue our relation to shared cultural forms, i.e., narratives, ideals, and values. Both thinkers find in Freud's anti-religious polemic a valuable attempt to address the intransigence, fanaticism, and violence that can result from an unreflected affirmation of Tradition. Alongside developing a respect and acceptance of other cultures, they argue for the need to establish a critical relation to sacred'meaning structures, one that mirrors interpretive strategies within the psychoanalytic process. Ricoeur and Castoriadis critique Freud's accentuation of neurosis while extending his thinking into personal-philosophical and social-political contexts.